PTTG: an important target gene for ovarian cancer therapy - Panguluri Siva; Yeakel Casey; Kakar Sham S (Journal of Ovarian Research, 2008)
Abstract Pituitary tumor transforming gene (PTTG), also known as securin is an important gene involved in many biological functions including inhibition of sister chromatid separation, DNA repair, organ development, and expression and secretion of angiogenic and metastatic factors. Proliferating cancer cells and most tumors express high levels of PTTG. Overexpression of PTTG in vitro induces cellular transformation and development of tumors in nude mice. The PTTG expression levels have been correlated with tumor progression, invasion, and metastasis. Recent studies show that down regulation of PTTG in tumor cell lines and tumors in vivo results in suppression of tumor growth, suggesting its important role in tumorigenesis. In this review, we focus on PTTG structure, sub-cellular distribution, cellular functions, and role in tumor progression with suggestions on possible exploration of this gene for cancer therapy.